Efektivitas Komunikasi Visual Gambar Peringatan Pada Kemasan Rokok Terhadap Kesadaran Kesehatan - Rio Rohmi Qushoyyi; Muhammad Ramdhani; Luluatu Nayiroh (Jurnal Ilmiah Wahana Pendidikan, 2023)
Research on the Effectiveness of Visual Communication of Warning Images on Cigarette Packaging Against Health Awareness (Correlational Descriptive Analysis on Students of the Faculty of Social and Political Sciences, Singaperbangsa University Karawang Class of 2018) aims to determine the visual perception of students of the Faculty of Social and Political Sciences, University of Singaperbangsa Karawang class of 2018 on images warnings about the dangers of smoking on cigarette packs. The research method used was quantitative with the population selected in this study being active students of the Faculty of Social and Political Sciences, Singaperbangsa University, Karawang class of 2018, both the Communication Studies Program and Government Science which consisted of 82 students. The results of the research and discussion show that the pictures of the dangers of smoking contained on cigarette packages are considered effective because they can be understood by the majority of informants and provide awareness to reconsider smoking activities while the health awareness of the dangers of smoking among the informants even though assessing the warning pictures on the dangers of smoking is not attractive, they will definitely paying attention to pictures of the dangers of smokers in every cigarette purchase, so that this gives them visual awareness of the dangers of smoking. Even though there is effectiveness in visual communication in the pictures of the dangers of smokers on each cigarette pack, most of the informants who incidentally are smokers decide not to stop smoking.